2022
DOI: 10.5194/wcd-3-361-2022
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating lightning in winter and summer with characteristics of the wind field and mass field

Abstract: Abstract. Lightning in winter (December–January–February, DJF) is rare compared to lightning in summer (June–July–August, JJA) in central Europe north of the Alps. The conventional explanation attributes the scarcity of lightning in winter to seasonally low values of variables that create favorable conditions in summer. Here we systematically examine whether different meteorological processes are at play in winter. We use cluster analysis and principal component analysis and find physically meaningful groups i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…It may be noted that the horizontal resolution of ERA5 data may not be sufficient to resolve the individual branches of updrafts and downdrafts. However, the signature of convection can be presented in the averaged vertical velocity value within the grid (Calvo‐Sancho et al, 2022; Morgenstern et al, 2023). The thunderstorms composites of vertical velocities are significantly lower than the previous observational (e.g., Adler & Fenn, 1979; Marshall et al, 1995) and modelling studies (e.g., Ogura & Takahashi, 1971; Osuri et al, 2017; Rotunno, 1981) and it could be mainly due to the coarser resolution of the ERA5 analysis and the layer of the averaging.…”
Section: Resultsmentioning
confidence: 99%
“…It may be noted that the horizontal resolution of ERA5 data may not be sufficient to resolve the individual branches of updrafts and downdrafts. However, the signature of convection can be presented in the averaged vertical velocity value within the grid (Calvo‐Sancho et al, 2022; Morgenstern et al, 2023). The thunderstorms composites of vertical velocities are significantly lower than the previous observational (e.g., Adler & Fenn, 1979; Marshall et al, 1995) and modelling studies (e.g., Ogura & Takahashi, 1971; Osuri et al, 2017; Rotunno, 1981) and it could be mainly due to the coarser resolution of the ERA5 analysis and the layer of the averaging.…”
Section: Resultsmentioning
confidence: 99%
“…This supports our finding of the very diverse wind-field thunderstorm conditions. Stucke et al (2022) relate our two thunderstorm types as described in Morgenstern et al (2022a) to upward lightning at two alpine towers and find that most upward lightning occurs in wind-field thunderstorm conditions. In general, thunderstorm frequencies under different synoptic conditions are often described (e.g., Wapler and James, 2015;Enno et al, 2014;Bielec, 2001;Kolendowicz, 2006) and regional thunderstorm differences are often subject of classical climatologies as mentioned in the introduction.…”
Section: Comparability Of the Found Thunderstorm Typesmentioning
confidence: 88%
“…Even though the European lightning patterns are in general well described (e.g., Wapler and James, 2015;Enno et al, 2014), it is less known how winter lightning differs meteorologically from lightning in summer. Morgenstern et al (2022a) found that thunderstorms in the cold season differ physically from thunderstorms in the warm season when studying a small observational region in northern Germany. They describe wind-field thunderstorms dominant in winter in contrast to CAPE (mass-field) thunderstorms typical for summer.…”
mentioning
confidence: 97%
“…Based on lightning measurements, recent studies have focused on climatologies of the electrical activity from a global perspective (e.g., Albrecht et al, 2016; Kaplan & Lau, 2021; Peterson et al, 2021; Virts et al, 2013) or continental scale, such as Asia (Dewan et al, 2018) and Europe (Morgenstern et al, 2022). In North America as part of the monsoon season, lightning records have been examined to identify areas of high frequency west of the SMO and over the GOC adjacent to the mainland of NWM (Holle et al, 2016; Holle & Murphy, 2015).…”
Section: Introductionmentioning
confidence: 99%